2018
DOI: 10.3917/inno.pr1.0042
|View full text |Cite
|
Sign up to set email alerts
|

Innovations sociales spontanées : mécanismes de contrôle émergents dans le crowdfunding

Abstract: Cet article a pour objectif de discuter des mécanismes de contrôle en œuvre dans les projets de crowdfunding et des innovations sociales spontanées qui en résultent. Les mécanismes de régulation issus des théories du contrôle semblent ici inopérants du fait de la faible implication financière des communautés de pourvoyeurs de ressources, de leur manque d’accès à l’information pertinente, et de leur atomicité. Ces mécanismes traditionnels sont remplacés par des innovations spontanées en termes de normes, de com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Future research needs to look at value management theories to see how they respond to such change oriented performance management (Chaboud et al, ). It may also be interesting to study this sector through the lens of organisational adaptation theory.…”
Section: Discussionmentioning
confidence: 99%
“…Future research needs to look at value management theories to see how they respond to such change oriented performance management (Chaboud et al, ). It may also be interesting to study this sector through the lens of organisational adaptation theory.…”
Section: Discussionmentioning
confidence: 99%
“…These mobile digital solutions take the form of C2C (consumer to consumer) community platforms and constitute a space for communication with user communities, in the sense of Tönnies et Harris (2001). As Chaboud et al (2018) have shown, these platforms possess the three constitutive elements of a community (Hillery, 1955): a shared concern (in this case wine), a common space (the platform in question, or any other virtual or even real space that makes exchanges possible) and a tendency to interact within this dedicated space. The resulting artifact allows for the nourishment and development of a common social capital (Adler et Kwon, 2002;Kwon et Adler, 2014) shared through the platform.…”
Section: Technology Uncertaintymentioning
confidence: 99%